Meta-omics profiling of full-scale groundwater rapid sand filters explains stratification of iron, ammonium and manganese removals. (15th April 2023) - Corbera-Rubio, Francesc; Laureni, Michele; Koudijs, Nienke; Müller, Simon; van Alen, Theo; Schoonenberg, Frank; Lücker, Sebastian; Pabst, Martin; van Loosdrecht, Mark C.M.; van Halem, Doris
Highlights: Single dual- and consecutive single-media filters are eco- and operationally equivalent. Both systems exhibited comparable performances and process compartmentalization. Media coating and genome-based composition were homogeneous in each compartment. Only protein abundances reflected stratification in activity. Backwash shapes microbial community distribution in rapid sand filters. Abstract: Rapid sand filters (RSF) are an established and widely applied technology for groundwater treatment. Yet, the underlying interwoven biological and physical-chemical reactions controlling the sequential removal of iron, ammonia and manganese remain poorly understood. To resolve the contribution and interactions between the individual reactions, we studied two full-scale drinking water treatment plant configurations, namely ( i ) one dual-media (anthracite and quartz sand) filter and ( ii ) two single-media (quartz sand) filters in series. In situ and ex situ activity tests were combined with mineral coating characterization and metagenome-guided metaproteomics along the depth of each filter. Both plants exhibited comparable performances and process compartmentalization, with most of ammonium and manganese removal occurring only after complete iron depletion. The homogeneity of the media coating and genome-based microbial composition within each compartment highlighted the effect of backwashing, namely the complete vertical mixing of the filter media. In stark contrast to this homogeneity, the removal of the contaminants was strongly stratified within each compartment, and decreased along the filter height. This apparent and longstanding conflict was resolved by quantifying the expressed proteome at different filter heights, revealing a consistent stratification of proteins catalysing ammonia oxidation and protein-based relative abundances of nitrifying genera (up to 2 orders of magnitude difference between top and bottom samples). This implies that microorganisms adapt their protein pool to the available nutrient load at a faster rate than the backwash mixing frequency. Ultimately, these results show the unique and complementary potential of metaproteomics to understand metabolic adaptations and interactions in highly dynamic ecosystems. Graphical abstract: Image, graphical abstract